Systematic Review: Recent Developments in Magnetic-Nanoparticle-Based DNA Extraction - Tjoa, Stanley Evander Emeltan; Mudasir, Mudasir; Suharyadi, Edi; Daryono, Budi Setiadi (UI Scholars Hub, 2025)
Deoxyribonucleic acid (DNA) is a research object for various molecular fields of study, and DNA extraction is a basic procedure in molecular biology laboratories. DNA extraction methods are evolving, from several steps using organic solvents to recent technology using magnetic nanoparticles as adsorbents for the purification step. The use of magnetic nanoparticles for DNA extraction is magnetizing because it is simple without heavy machinery, such as centrifugation and organic solvents. The application of this method is extensive and diverse. This systematic review summarizes current development trends for some aspects of this DNA extraction system from the magnetic nanoparticle synthesis method, extraction protocol, and different types of samples used. The main purpose of this review is to provide an overall perspective of the use of magnetic nanoparticles in DNA extraction for researchers to start their exploration of this safe, simple, and rapid technique. In general, the most well-known magnetic nanoparticle preparation uses the coprecipitation method. The preferred particle is a plain and silica-coated magnetic nanoparticle using tetraethyl orthosilicate. The most common buffer systems for binding, washing, and elution are Polyethylene Glycol (PEG) and NaCl, 70% ethanol, and Tris–EDTA, respectively. The extraction system with magnetite can be used for various types of samples, ranging from human specimens to animal, plant, and bacterial specimens. The extraction yields using the magnetic-nanoparticle-based method were between 0.03 µg and 116.63 µg with a DNA purity ratio between 1.09 and 1.99.